2010
DOI: 10.5851/kosfa.2010.30.5.804
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Protease-Producing Bacterium, Bacillus amyloliquefaciens P27 from Meju as a Probiotic Starter for Fermented Meat Products

Abstract: This study was performed to select protease-producing Bacillus sp. as a potential probiotic starter for fermented meat products. In order to isolate protease-producing bacterium from meju, measured the diameter of the clear zone on agar plate (TSA, 1% (w/v) skim milk) and analyzed for intracellular protease activity, then 10 Bacillus-like strains were isolated. Three Bacillus-like strains (P19, P27, and P33) among 10 strains were able to tolerate in acidic condition (TSB, pH 2.5, 2 h incubation). These 3 strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Protease activity of Bacillus was determined using the method described by Lee et al [21] with some modifications. Briefly, 1 mL of the culture supernatant was reacted with 1 mL of 0.6% casein solution (in 0.05 M potassium phosphate buffer, pH 7.5) at 37°C for 10 min.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…Protease activity of Bacillus was determined using the method described by Lee et al [21] with some modifications. Briefly, 1 mL of the culture supernatant was reacted with 1 mL of 0.6% casein solution (in 0.05 M potassium phosphate buffer, pH 7.5) at 37°C for 10 min.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…Shahzadi et al (2019) reported that this species can degrade long chained hydrocarbons, producing small metabolites. Other enzymes described to occur in B. amyloliquefaciens strains include chitinases (Wang et al, 2002), proteases (Lee et al, 2010) and laccases (Pan et al, 2011). This, in fact, may help plant growth by accelerating decomposition of organic residues (even the more chemically complex ones) and nutrient mineralization.…”
Section: Discussionmentioning
confidence: 99%